Malting Millets: Unlocking Enhanced Bioavailability of Nutrients - Patil Shweta A.; Udachan Iranna S. (BIO Web of Conferences)
Millets, naturally rich in nutrients, possess inherent anti-nutritional factors that limit bioavailability. Malting is a bioprocessing technique that enhances the nutritional value of grains by activating enzymes and reducing anti-nutritional factors. The present study investigated the impact of varying malting durations (24-72 hours, 24±2°C) on the nutritional profile of finger millet, pearl millet, and sorghum. The research focused on optimizing malting (24-72 hours) for finger millet, pearl millet, and sorghum in enhancing nutritional profile of millet malt. Malting induced hydrolytic activity, leading to a reduction in protein (15-35%) and carbohydrate (20-40%) content, attributed to protease activation and respiratory utilization of soluble sugars, respectively. Conversely, reducing sugars increased (12-15%). This suggests that germination utilizes soluble sugars and activates proteases, improving protein bioavailability. Mineral analysis revealed a biphasic response, with an initial decrease followed by an increase in mineral content with prolonged malting. It showed an initial decrease at 24 hours, followed by an increase at 36 and 48 hours. The findings indicate that malted millet flours, rich in fibre, calcium, and iron, are promising ingredients for gluten-free extruded products with their enhanced nutritional profile and low glycaemic index. Thus, this research underscores the potential of malting to improve the nutritional quality of millets by enhancing nutrient bioavailability and reducing anti-nutritional factors, making them promising ingredients for nutrient-dense and gluten-free products.